Estudo das técnicas de obtenção de Hamiltonianos efetivos em Óptica Quântica - Carvalho, Camila Miranda (2009)
In the Quantum Optics area, the construction of effective hamiltonian is a matter of great importance, since from them we can generate and manipulate quantum states and logical operations. In this work we discuss 3 approximate methods for obtaining such effective hamiltonians: i) adiabatic elimination, ii) method of effective dynamics for oscillating hamiltonians and iii) nonlinear small rotations. Here we analyze the regime of validity of these techniques, their disadvantages and advantages. We note that, although adiabatic elimination is the most used and known, it has inconsistencies and can provide incorrect effective hamiltonians. The method of effective dynamics, although a very simple technique, also has inconsistencies and is not applicable to dissipative systems. Moreover, the method of nonlinear small rotations, which appears as the most accurate, is rarely used in the literature.